2018
DOI: 10.1101/436253
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Defining the RNA Interactome by Total RNA-Associated Protein Purification

Abstract: UV crosslinking can be used to identify precise RNA targets for individual proteins, transcriptome-wide. We sought to develop a technique to generate reciprocal data, identifying precise sites of RNA-binding proteome-wide. The resulting technique, total RNA-associated protein purification (TRAPP), was applied to yeast (S. cerevisiae) and bacteria (E. coli). In all analyses, SILAC labelling was used to quantify protein recovery in the presence and absence of irradiation. For S. cerevisiae, we also compared cros… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 102 publications
2
31
1
Order By: Relevance
“…3c ). This is consistent with a recent study that identified Ede1 as a potential RNA-binding protein 22 . To confirm that Ede1 is regulating ADC17 mRNA at the level of translation, we deployed the SunTag labelling method 23 .…”
Section: Resultssupporting
confidence: 93%
“…3c ). This is consistent with a recent study that identified Ede1 as a potential RNA-binding protein 22 . To confirm that Ede1 is regulating ADC17 mRNA at the level of translation, we deployed the SunTag labelling method 23 .…”
Section: Resultssupporting
confidence: 93%
“…While ATP was known to bind to a variety of proteins in several organisms (Reinhard et al , ; Geer & Fitzgerald, ; Piazza et al , ), promiscuous binding of GTP was reported only recently (Piazza et al , ). The frequent binding of purine nucleotides does not appear to be explained by propensity of specific proteins for RNA binding, since we found no correlation with RNA binding enzymes from two recently published E. coli studies (Queiroz et al , ; Shchepachev et al , ). The recent discovery of purine nucleotide function as biological hydrotropes (Patel et al , ) could offer an explanation; however, effects on protein aggregation were only observed at much higher concentrations than used in our assay (> 5 mM compared to 0.2 mM).…”
Section: Discussioncontrasting
confidence: 73%
“…Different approaches are available to study RNA–protein interactions from a protein-centric view (to identify novel RNA-binding proteins and domains) or from an RNA-centric view (to identify novel RNA targets of specific RNA-binding proteins (RBP)). The latter group of methods, e.g., CLIP-Seq (cross-linking immunoprecipitation-high-throughput sequencing), involves next-generation sequencing after affinity purification of an RBP cross-linked to its target RNAs. − In contrast, protein-centric analyses identify proteins bound to a specific RNA or a subset of RNAs employing, e.g., cross-linking by UV light and mass spectrometry. ,− Such a method was used to characterize the mRBPome by cross-linking mRNA-bound proteins and subsequent purification of mRNAs by oligo-dT chromatography . The specific amino acid residue that cross-linked to an RNA is identified using mass spectrometry .…”
Section: Introductionmentioning
confidence: 99%